Pengembangan Potensi Masyarakat Melalui Pelatihan dan Pertunjukan Musik di Desa Cisaat, Subang - Saputra, Dani Nur; Herdiati, Dian; Saryanto, Saryanto; Srimoko, Gandung Joko; Ratna, Ni Gusti Ayu Ary; Mahardhika, Galah Akbar; Elisa, Elisa; Susilawaty, Ezra; Agustina, Halimah (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2024)
The village of Cisaat in Subang, West Java has sufficient natural potential to make it a tourist destination. The existence of the village needs support from local artistic potential, so that Cisaat can offer natural beauty and artistry that bring aesthetic value. The community must possess the necessary skills to bring art to the village of Cisaat. The current artistic culture in Cisaat still needs development as it has great potential. This village has quite a few inhabitants in the children and teenage age groups. They have great potential to develop and advance Cisaat village as a tourist destination. The partner's problem is the limited number of human resources with experience and background in music. Art education in Cisaat village is still conducted traditionally, with elders only passing down their artistic skills to their own family members. There are many children and teenagers who cannot play music, they only watch and are not involved in artistic activities in the village. The community service events equip the society with music playing skills. The skills acquired potentially create opportunities for developing the community's artistic and tourism potentials. The activities offer benefits towards elevating the cultural and artistic sectors in Cisaat village.